Abaro / Nor Zhafira Adlina Mohammad Mazani - Mohammad Mazani, Nor Zhafira Adlina (2020)
Resta Enterprise Sdn. Bhd has established since year 2001, with more than 15 years experience in footwear trading as one of the footwear in Malaysia. We always adhere strongly to our vision, mission and goal in achieving service, customer relationship and corporate social responsibility. Abaro mainly focuses on school with lifestyle concept concerning fashion, colors and students need.